2017
DOI: 10.2151/sola.2017-017
|View full text |Cite
|
Sign up to set email alerts
|

Air Particulate Pollution in Ulaanbaatar, Mongolia: Variation in Atmospheric Conditions from Autumn to Winter

Abstract: Ulaanbaatar, the capital city of Mongolia, is subject to high levels of atmospheric pollution during the winter, which severely effects the health of the exposed population. Using lidar and ground level meteorological observations, we studied the temporal variation of the PM 2.5 and the structure of the atmospheric boundary layer (ABL) during the 2010 heating season. The concentration of PM 2.5 increased after the air temperatures sharply decreased during two cold waves occurring 8−10 and 21−25 October. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The maximum atmospheric boundary layer height continuously decreased from summer to winter. Stable atmospheric conditions and a surface inversion layer in the winter resulted in low wind velocities (<2 m·s −1 ), especially at night as reported by the previous study [38]. Consequently, because of both the meteorological and topographical conditions, air pollutants remained stagnant at the urban surface level, which resulted in high concentrations of PM 2.5 in the winter as shown in Table 2.…”
Section: Resultsmentioning
confidence: 58%
“…The maximum atmospheric boundary layer height continuously decreased from summer to winter. Stable atmospheric conditions and a surface inversion layer in the winter resulted in low wind velocities (<2 m·s −1 ), especially at night as reported by the previous study [38]. Consequently, because of both the meteorological and topographical conditions, air pollutants remained stagnant at the urban surface level, which resulted in high concentrations of PM 2.5 in the winter as shown in Table 2.…”
Section: Resultsmentioning
confidence: 58%
“…This stagnation increases the relative concentration of PM 2.5 because of the continuous influx of air pollutants from household and vehicular emissions. Studies in India, 34 Mongolia, 35 and California/United States 36 showed similar variability in PM 2.5 by season. In these countries, PM 2.5 concentration during the wet months exceeded concentrations during months when rainfall and/or relative humidity were high.…”
Section: Discussionmentioning
confidence: 74%
“…Papers discussing this issue in Poland are not rare to find, e.g., Dordevic et al (2011) analyzed the effects of pollutant emission from district heating systems on the correlation between air quality and health risk. Wang et al (2017) took Ulaanbaatar, Mongolia as an example and analyzed the levels of PM2.5 in 2010 heating season and found out a significant increase when the heating season came. Guttikunda (2008) also pointed out that heating was one of the main factors influencing the air quality of Ulaanbaatar.…”
Section: Literature Reviewmentioning
confidence: 99%